2021
DOI: 10.1021/acs.organomet.1c00150
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylic-Carbon-Centered Mechanism for Catalytic α-Methylation

Abstract: The multicarbonyl manganese pincer complex-catalyzed α-methylation reaction is studied. In this theoretical work, an unprecedented carbonylic-carbon-centered mechanism is discovered. That is, the catalytic center is on the carbonyl ligand instead of the metal atom, such as the common aromatization/dearomatization metal–ligand cooperation mechanism. Further, the origins of chemoselectivity of enone hydrogenation are addressed with the $DEL-type NBO analyses. With a manganese pincer catalyst, the donor–acceptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…The second cycle partially follows the mechanism proposed by Schaeffer and co-workers . As mentioned previously (vide supra), at the initial stages of the reaction, the base plays no crucial role in the dehydrogenation of methanol which contrasts with their findings.…”
Section: Results and Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The second cycle partially follows the mechanism proposed by Schaeffer and co-workers . As mentioned previously (vide supra), at the initial stages of the reaction, the base plays no crucial role in the dehydrogenation of methanol which contrasts with their findings.…”
Section: Results and Discussionsupporting
confidence: 66%
“…Because complex 3 is an active catalyst, it enabled us to investigate whether the hydrogenation of the α,β-unsaturated ketone intermediate is dependent on a base. Recently, computational studies have shown that in manganese tricarbonyl complexes, the axial carbonyl ligand serves as the catalytic center in conjunction with active participation of the cesium cation of the used base (Cs 2 CO 3 ) . Although during our optimization experiments, we have shown that different bases can be used (Table ), we wanted to know if complex 3 can hydrogenate the intermediate 2-methyl-1-phenylprop-2-en-1-one with the in situ generated hydrogen.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with our previous theoretical studies on homogeneous catalytic reactions, all computations in this study were carried out by the density functional theory method with ωB97X-D functional using the Gaussian 09 program . Geometries were optimized in the 1,4-dioxane solvent using the BS-I basis sets, where the 6-311G­(d,p) basis sets were used for nonmetal atoms and the SDD basis sets with effective core potentials were used for metal atoms. , The single-point energy refinements were further performed with BS-II basis sets, where the 6-311++G­(2d,p) basis sets were used for nonmetal atoms, and the SDD basis sets were used for metal atoms.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with our previous theoretical studies, this research was carried out with the DFT ωB97X-D method using the Gaussian 09 program . Geometries were optimized in the THF solvent using the def2-SVP basis sets. , The single-point energy refinements were further performed with the def2-TZVPP basis sets. , Thermal corrections and entropy contributions to the Gibbs free energies were obtained with the ωB97X-D/def2-SVP method.…”
Section: Methodsmentioning
confidence: 99%